Impact of finasteride on modulating the risk and clinical outcomes of bladder cancer: insights from a comprehensive meta-analysis - Yu, Ailing; Bai, Zian; Wang, Yijie; Luo, Zhen; Du, Xiaochen; Chen, Mengxin; Wen, Shuang; Wang, Honglong; Yuan, Xiaoying; Yang, Chunyu; Bai, Shanshan; Fan, Bo (Frontiers in Pharmacology, 2025)
PurposeNumerous prior analyses have highlighted a potential link between androgen suppression therapy (AST) and bladder cancer (BCa). However, there is a notable gap in research specifically examining the influence of finasteride on BCa risk and clinical outcomes. This study aimed to evaluate preventive and therapeutic value of finasteride for BCa patients.MethodsThis meta-analysis adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Guidelines. The PubMed, Embase, Cochrane Library, and Web of Science databases were searched up to 20 December 2024, to identify studies that examined the intake of finasteride and its impact on the incidence and clinical prognosis of patients with BCa. Data was extracted for further analysis by two different reviewers who independently examined the titles and abstracts of the included articles. Subgroup analyses and leave-one-out sensitivity analyses, were applied to mitigate the potential confounding factors associated with heterogeneity.ResultsOur investigation revealed that finasteride markedly decreased the likelihood of developing BCa (hazard ratio [HR]: 0.75, 95% confidence interval [CI]: 0.63–0.88). Subgroup analyses indicated that the preventive effect of finasteride in BCa incidence were generally consistent, regardless of study region, types of research. Furthermore, no notable disparities were observed in OS, CSS, or RFS between the finasteride group and the control group.ConclusionFinasteride plays a protective role against the progression of BCa, nevertheless, its effects on prognostic outcomes, including OS, CSS, and RFS, remain inconclusive. Additional multi-center prospective studies with long-term follow-up are required to further validate prophylactic role of finasteride on bladder cancer.Systematic review registration numberhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=525046, identifier CRD42024525046.